COVID-19 response in northwest Syria: innovation and community engagement in a complex conflict. (21st May 2020) - Ekzayez, Abdulkarim; al-Khalil, Munzer; Jasiem, Mohamad; Al Saleh, Raed; Alzoubi, Zedoun; Meagher, Kristen; Patel, Preeti
ABSTRACT: Despite lacking capacity and resources, the health system in the northwest Syria is using innovative approaches for the containment of COVID-19. Lessons drawn from previous outbreaks in the region, such as the polio outbreak in 2013 and the annual seasonal influenza, have enabled the Early Warning and Response Network, a surveillance system to develop mechanisms of predicting risk and strengthening surveillance for the new pandemic. Social media tools such as WhatsApp are effectively collecting health information and communicating health messaging about COVID-19. Community engagement has also been scaled up, mobilizing local resources and encouraging thousands of volunteers to join the 'Volunteers against Corona' campaign. Bottom-up local governance technical entities, such as Idleb Health Directorate and the White Helmets, have played key leadership role in the response. These efforts need to be scaled up to prevent the transmission of COVID-19 in a region chronically affected by a complex armed conflict.